Taiwan in troubled times : essays on the Chen Shui-bian presidency - Copper, John Franklin (World Scientific, 2002)
Taiwan in Troubled Times is concerned with Taiwan's politics and its relations with China following the election of Chen Shui-bian as President in March 2000. This event created problems between Taiwan and China and led to political gridlock in Taiwan. The Chen Administration is evaluated in this book. So is President Chen's party, which evolved as an opposition party and is now in power but is unaccustomed to the role.